New Methodology for Asynchronous Motor the Adaptive-Sliding-Mode-Control Capable of High Performance Regulation - Mahfoudh Mohamed Abderrahmane Hbib; Ouissam Belghazi; Moulay Rachid Douiri; Mohamed Cherkaoui (Universitas Ahmad Dahlan, 2018)
A new methodology for the design of adaptive sliding mode control (ASMC) for Asynchronous motor control will be presented in this paper. The sliding mode control (SMC) has become one of the most active branches of control theory that has found successful applications in a variety of engineering systems, such an the electrical motors. The new Adaptive sliding mode control method is compared to other existing techniques. The pros and cons of ASMC controller will be demonstrated by intensive simulation results. It will be shown that the presented controller is with fast tracking capability, less steady state error, and robust to load disturbance.